Phonetic Variance of /d/ and /r/ in Hebrew in Late Antiquity. (20th July 2022) - Howard, Jonathan
Abstract: A common type of textual variant in Hebrew is the alternation of ד and ר. Such variance has traditionally been attributed to scribes and confined to the written layer of transmission. However, given the articulatory proximity of / d / and / r /, orally-induced variance should also be considered. I present several instances in Hebrew and Aramaic, where the context suggests that the two letters were confused in speech. This in turn sheds light on two other matters: first, it offers a new point of view for examining the question of the two allophones of / r / reported in the Tiberian Masoretic tradition, seemingly in support of Aron Dotan's view on the matter; second, it removes one of the difficulties raised against Yaacov Sussman's theory about the orality of the Mishna in the Amoraic period, by reducing a scribal variant (צוערי/סועדי) to a phonetic one.